A high-uniform closed-cell silicone foamed silica gel and a preparation method thereof
Patent Information
- Application Number
- CN202611144949.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-16
AI Technical Summary
[0007]本发明的目的是提供一种高均匀闭孔型有机硅发泡硅胶及其制备方法,解决了传统有机硅发泡过程中因交联与发泡反应速率难以协同匹配,从而导致材料内部泡孔塌陷、孔径不均以及闭孔率低下的问题
[0060] 1. This invention solves the problem of mismatch between foaming and crosslinking kinetics by introducing a two-stage inhibitor system in combination with inert nucleating seeds and a slow-release hydroxyl source. The alkynol and thermally desorbed masking agent construct three temperature windows, allowing the system to undergo safe mixing, delayed expansion and rapid crosslinking lock in sequence, achieving an orderly relay of foaming and crosslinking. At the same time, the introduction of heterogeneous nucleation sites makes bubble nucleation more controllable and avoids homogeneous boiling, thereby obtaining a highly uniform cell structure.
Smart Images

Figure CN122917544A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of organosilicon polymer materials technology, and in particular to a highly uniform closed-cell organosilicon foamed silicone and its preparation method. Background Technology
[0002] Existing silicone foam materials are mainly divided into condensation-type room temperature vulcanization systems, peroxide vulcanization compound systems, and addition-type liquid foaming systems.
[0003] Condensation-type room temperature vulcanizing foaming systems typically use hydroxyl-terminated silicone raw rubber as the base adhesive, adding hydrogen-containing silicone oil. Crosslinking and foaming are simultaneously achieved through a condensation-dehydrogenation reaction under the action of organotin or titanium ester catalysts. The curing process of this system is significantly affected by ambient temperature and humidity, making it difficult to control the competing processes of cell growth and crosslinking. Furthermore, the condensation reaction relies on the diffusion of moisture from the external environment into the interior, hindering deep curing and leading to inconsistent curing levels between the inner and outer layers in thick-section products. These factors result in poor cell uniformity and density fluctuations in the products, making it difficult to provide a stable sealing and bonding effect in practical applications.
[0004] The peroxide-cured compound foaming system uses methyl vinyl silicone rubber raw rubber as the base material and adds reinforcing fillers such as fumed silica. Peroxide is used as the vulcanizing agent, combined with a chemical foaming agent for high-temperature molding and foaming. This system produces halogen-containing or acidic byproducts during peroxide decomposition, releasing irritating gases and posing a corrosion risk to metal components such as copper, making it difficult to meet environmental and electrical regulations in the new energy vehicle and electronics manufacturing sectors. Furthermore, the chemical foaming agent has a narrow decomposition temperature window and high heat release, making it prone to cell merging, rupture, or collapse during foaming, resulting in a density gradient within the product.
[0005] Addition-type platinum-catalyzed liquid foaming systems are widely used due to their entirely addition-reaction nature and lack of corrosive byproducts. This system primarily uses vinyl-terminated polydimethylsiloxane as the base polymer and hydrogen-containing silicone oil as the crosslinking agent. Under the action of a platinum catalyst, a hydrosilylation reaction occurs to form a crosslinked network; simultaneously, a hydroxyl source is introduced to react with excess silanol groups, resulting in dehydrogenation and the generation of hydrogen gas for foaming. However, in practical applications, due to the high activity of the platinum catalyst, a mismatch between crosslinking and foaming kinetics often occurs.
[0006] On the one hand, this manifests as premature cross-linking, where the cross-linking network forms before bubbles have fully nucleated or grown; on the other hand, it manifests as premature foaming, where bubbles expand rapidly even when the compound is at a low viscosity. This mismatch leads to interconnected, merged, or collapsed cells, reducing the closed-cell rate and causing surface peeling and cracking of the product. Furthermore, because conventional systems lack cell wall strengthening mechanisms, the closed cells formed are prone to cell wall rupture under heat or pressure. The resulting microstructural defects from gas escape reduce the effective cross-linking density, increase the compression set of the product, and fail to meet the precision sealing and lightweight cushioning requirements of specific environments. Summary of the Invention
[0007] The purpose of this invention is to provide a highly uniform closed-cell silicone foam and its preparation method, which solves the problems of poor matching between crosslinking and foaming reaction rates in traditional silicone foaming processes, resulting in collapsed internal cells, uneven pore size, and low closed-cell rate.
[0008] To achieve the above objectives, the present invention provides the following technical solution:
[0009] In a first aspect, the present invention provides a highly uniform closed-cell silicone foaming material, which adopts the following technical solution:
[0010] It is made by mixing component A and component B in a mass ratio of 100:(4-10) and then subjecting them to foaming vulcanization;
[0011] Component A comprises the following raw materials in parts by weight:
[0012] Vinyl-terminated polydimethylsiloxane: 100 parts;
[0013] Hydrophobically treated fumed silica: 8-20 parts;
[0014] Vinyl functionalized MQ silicone resin pre-diluted solution: 0.5-3.0 parts;
[0015] Inert nucleating seed crystals: 0.3-2.0 parts;
[0016] Microencapsulated silanol complex: The amount added is such that the molar ratio of Si-H functional groups to active OH equivalents after mixing component A and component B is 1:(0.3~0.6).
[0017] Platinum catalyst: The amount added is such that the mass concentration of metallic platinum in component A is 3-12 ppm;
[0018] First inhibitor: 0.05-0.3 parts;
[0019] Second inhibitor: 0.02-0.15 parts;
[0020] Component B is a compound mixture of hydrogen-containing silicone oil and the terminal vinyl polydimethylsiloxane. The amount of hydrogen-containing silicone oil is adjusted so that the total Si-H / vinyl functional group molar ratio after mixing component A and component B is (1.5~3.0):1.
[0021] By adopting the above technical solution, the present invention constructs a reaction system in which the foaming rate and crosslinking rate are decoupled and precisely synchronized under specific conditions, thereby obtaining an organosilicon foam with uniform cell structure and high closed-cell rate.
[0022] The specific reaction mechanism proceeds as follows:
[0023] Two types of core chemical reactions within the system are identified. One type is a chemical foaming reaction, in which the diphenylsilanediol core material released from the microencapsulated silanol complex provides active hydroxyl groups, which undergo dehydrogenation condensation with the silanium bonds in the hydrogen-containing silicone oil under platinum catalysis, continuously generating hydrogen gas. The other type is a network crosslinking reaction, in which the vinyl groups in the vinyl-terminated polydimethylsiloxane and vinyl-functionalized MQ silicone resin undergo addition reactions with the silanium bonds in the hydrogen-containing silicone oil, constructing a three-dimensional solid framework for silicone rubber.
[0024] During room temperature storage and the initial mixing stage, the inhibition and isolation systems work synergistically. The first and second inhibitors jointly occupy the active sites of the platinum catalyst, locking in catalytic activity; simultaneously, the capsule wall of the microencapsulated silanol complex physically isolates the internal hydroxyl source from the external hydrogen-containing silicone oil. During this stage, both foaming and crosslinking reactions are in a dormant state, preventing early thickening or disordered gas evolution of the adhesive.
[0025] During the heating, foaming, and vulcanization stage, the system exhibits a stepwise thermal response. As the temperature rises, the second inhibitor reaches its dissociation temperature and detaches from the platinum catalyst, initiating the hydrosilylation reaction and causing the apparent viscosity of the rubber compound to increase.
[0026] Simultaneously, the capsule walls of the microencapsulated silanol complex reach their breaking temperature and melt and rupture, releasing the internal silanol core material, which undergoes dehydrogenation condensation with the silicon-hydrogen bonds to generate hydrogen gas. Since the adhesive matrix already possesses a certain viscosity and melt strength at this point, it can effectively encapsulate the released hydrogen gas, preventing the migration, bubbling, and overflow of gas molecules, thereby creating a uniform and independent closed-cell structure in situ within the silicone.
[0027] Preferably, the vinyl-terminated polydimethylsiloxane has a vinyl-terminated structure at both ends, a viscosity of 3,000–30,000 mPa·s, and a vinyl content of 0.10–0.25 wt%.
[0028] The hydrophobically treated fumed silica is surface-treated with hexamethyldisilazane or tetramethyltetravinylcyclotetrasiloxane and has a BET specific surface area of 150–300 m².2 Fumed silica with a surface Si-OH residue of less than 0.5% per g.
[0029] By adopting the above technical solution, the residual silanol content on the surface of fumed silica treated with specific hydrophobicity is extremely low, cutting off the pathway for the disordered hydrogen evolution reaction between the hydroxyl groups on the silica surface and the hydrogen-containing silicone oil under the action of a catalyst. This ensures that the foaming gas source originates solely from the microencapsulated silanol complex, improving the controllability of the foaming process and preventing the formation of disordered pores of varying sizes in the material matrix.
[0030] Preferably, the M / Q value of the MQ silicone resin in the vinyl-functionalized MQ silicone resin pre-diluted solution is 0.65 to 0.85, the vinyl content is 0.5 to 2.0 wt%, and the vinyl-functionalized MQ silicone resin in the vinyl-functionalized MQ silicone resin pre-diluted solution is dissolved in the end-vinyl polydimethylsiloxane in a semi-transparent dispersion state.
[0031] The inert nucleating seed crystals are ultrafine talc powder surface-treated with KH-560 silane coupling agent. 50 The particle size is 1–5 μm.
[0032] By adopting the above technical solution, vinyl-functionalized MQ silicone resin participates in network construction as a multifunctional crosslinking node, thereby improving the tensile strength and tear resistance of the cell wall after curing.
[0033] Ultrafine talc powder treated with a specific silane coupling agent is uniformly dispersed in a silica matrix. As a heterogeneous nucleating agent, it reduces the nucleation free energy of the gas, causing the generated hydrogen to preferentially precipitate and nucleate uniformly on the surface of the tiny seed crystals, thereby increasing the pore density and reducing the size of individual pores.
[0034] Preferably, the first inhibitor is 1-ethynyl-1-cyclohexanol or 3,5-dimethyl-1-hexyn-3-ol;
[0035] The second inhibitor is a triphenylphosphine-platinum coordination complex that dissociates at 70–95 °C or a reversible complex formed by a sterically hindered phenol and platinum;
[0036] The hydrogen-containing silicone oil has a Si-H content of 0.8–1.8 wt% and a viscosity of 15–80 mPa·s.
[0037] By adopting the above technical solution, the first inhibitor and the second inhibitor constitute a compound inhibition system with different temperature ranges. The first inhibitor provides a basic room-temperature applicable period, while the second inhibitor utilizes the thermosensitive dissociation characteristics of the coordination complex at 70 to 95°C to achieve temperature-controlled catalytic activity, enabling the acceleration node of the cross-linking reaction to overlap and match the microcapsule cell disruption and gas release node.
[0038] Preferably, the cell wall disruption temperature of the microencapsulated silanol complex is 85–100°C; the preparation method of the microencapsulated silanol complex includes:
[0039] Diphenylsilanediol, used as the core material, methyl methacrylate monomer, used as the wall material prepolymer, and a crosslinking agent are mixed at a core-to-wall mass ratio of 1:(0.5-2.0) to obtain a mixture.
[0040] The mixture is then added to an aqueous solution containing polyvinyl alcohol dispersant and homogenized to form a microemulsion; subsequently, an initiator is added to the microemulsion and the mixture is polymerized and coated at a constant temperature of 50–80°C.
[0041] By employing the above technical solution, microcapsules using polymethyl methacrylate crosslinked networks as wall materials undergo phase transition softening and rupture in the range of 85 to 100°C. This rupture temperature range strictly matches the dissociation range of the thermosensitive inhibitor, ensuring that foaming gas only begins to be generated in large quantities when the crosslinked network has initial skeletal strength, thus solving the problem of premature foaming leading to bubble collapse and rupture from the material source.
[0042] Preferably, the platinum catalyst is a diluent of Karstedt catalyst with terminal vinyl polydimethylsiloxane containing 3000-8000 ppm Pt.
[0043] By adopting the above technical solution, the platinum catalyst dilution solution of a specific concentration takes into account the catalytic requirements of both hydrosilylation and dehydrogenation condensation reactions, ensuring the thoroughness of the chemical reaction in the thermosetting molding stage and avoiding the impact of unreacted functional groups on the later aging resistance of the product.
[0044] Secondly, the present invention provides a method for preparing highly uniform closed-cell silicone foam, employing the following technical solution:
[0045] A method for preparing a highly uniform closed-cell silicone foam, used to prepare the highly uniform closed-cell silicone foam described in the first aspect above, includes the following steps:
[0046] Add the vinyl-terminated polydimethylsiloxane into the stirring equipment, and under the protection of nitrogen, add the hydrophobically treated fumed silica and the pre-diluted vinyl-functionalized MQ silicone resin in batches, and stir to obtain a uniform paste.
[0047] Subsequently, inert nucleating seeds, microencapsulated silanol complex, platinum catalyst, first inhibitor, and second inhibitor were added to the homogeneous paste. The mixture was then degassed and stirred under vacuum conditions and stored in a light-proof, sealed container to obtain component A.
[0048] The hydrogen-containing silicone oil was compounded and mixed with the vinyl-terminated polydimethylsiloxane, and then vacuum degassed and sealed to obtain component B.
[0049] The obtained component A and component B are dynamically degassed and mixed at a mass ratio of 100:(4-10) to obtain the adhesive compound;
[0050] The rubber compound is injected into a mold for foaming and vulcanization. Finally, after demolding, trimming, and inspection, a highly uniform closed-cell silicone foam is obtained.
[0051] By adopting the above technical solution, the filler is added in batches and the components are prepared in stages, ensuring the macroscopic uniformity of the material dispersion within the matrix. The inorganic filler is mixed under nitrogen protection to prevent environmental moisture from entering and participating in disordered side reactions.
[0052] The microcapsule complex and sensitive additives such as catalysts are added under vacuum conditions in the later stages, avoiding abnormal microcapsule breakage or premature inhibitor deactivation caused by high-speed shear friction and heat generation. The mixing process combined with vacuum degassing eliminates macroscopic mechanical bubbles present inside the rubber compound, allowing the final foamed structure to be formed by micropores generated through chemical reactions.
[0053] Preferably, in the process of obtaining component A, the vacuum condition is -0.095 MPa, the degassing and stirring time is 20 min, and the obtained component A is stored in an environment not exceeding 25°C.
[0054] By adopting the above technical solutions and strictly controlling the vacuum level and material temperature, free air entrained during the stirring process is eliminated, and the negative impact of the mechanical heat of the equipment on heat-sensitive raw materials is eliminated, thus maintaining the long-term latent stability of the foaming system.
[0055] Preferably, the foaming vulcanization process includes the following steps: preheating expansion at 75–95°C for 60–180 seconds; cross-linking molding at 130–165°C for 3–8 minutes; and post-curing treatment at 180–200°C for 30–60 minutes.
[0056] By adopting the above technical solution, the three-step temperature control program matches the chemithermal response of the microcapsules and inhibitors. The first stage, preheating expansion, triggers capsule wall breaking and catalyst dissociation, completing the initial nucleation and microscopic growth of bubbles; the second stage, cross-linking molding, utilizes the sudden increase in high temperature to dramatically increase the addition reaction rate, rapidly solidifying the cell skeleton and locking the closed-cell morphology; the third stage, post-curing treatment, eliminates internal residual stress and volatilizes low-molecular-weight oligomers, improving the dimensional stability of the product.
[0057] Preferably, the dynamic degassing and mixing time is controlled to be 15-50 seconds, and then the adhesive is immediately injected into a mold preheated to 75-95°C.
[0058] By adopting the above technical solution, the efficient mixing in a short time prevents excessive latent reaction from occurring at room temperature after the two components are mixed. The rubber material is directly injected into the preheated mold to establish a temperature gradient from the outside to the inside, which promotes the rapid cross-linking and skin formation of the silicone near the mold wall area. This tightly seals the gas generated by subsequent deep foaming inside the product, improving the surface smoothness and overall closed-cell rate of the product.
[0059] In summary, the present invention has at least one of the following beneficial technical effects:
[0060] 1. This invention solves the problem of mismatch between foaming and crosslinking kinetics by introducing a two-stage inhibitor system in combination with inert nucleating seeds and a slow-release hydroxyl source. The alkynol and thermally desorbed masking agent construct three temperature windows, allowing the system to undergo safe mixing, delayed expansion and rapid crosslinking lock in sequence, achieving an orderly relay of foaming and crosslinking. At the same time, the introduction of heterogeneous nucleation sites makes bubble nucleation more controllable and avoids homogeneous boiling, thereby obtaining a highly uniform cell structure.
[0061] 2. This invention improves mechanical properties and dimensional stability while achieving high foaming ratio by adding vinyl-functionalized MQ silicone resin to the system. The resin can be enriched and cross-linked in situ at the cell wall interface during the foaming and vulcanization process, increasing the thickness uniformity and structural toughness of the closed-cell wall film. Based on the enhanced cross-linking network and high closed-cell ratio, the internal stress distribution of the material is more uniform when under pressure, reducing the compression set of the product and achieving a balance between lightweight and mechanical strength.
[0062] 3. This invention adopts a halogen-free addition reaction route throughout the process, which has excellent environmental safety and industrial production adaptability. The formula does not require the addition of chemical foaming agents such as azo compounds that are easy to decompose and produce toxicity. There is no release of acidic or toxic byproducts during the production process. This not only meets high standards of environmental protection and occupational health requirements, but also completely eliminates the risk of corrosion of molds and processing equipment by harmful byproducts. The overall process is stable and easy to achieve large-scale mass production. Attached Figure Description
[0063] Figure 1 This is a rheological comparison diagram of the complex viscosity of the high uniformity closed-cell silicone foaming silicone of the present invention and the comparative example mixed adhesive as a function of test time.
[0064] Figure 2 This is a differential scanning calorimetry waveform of the mixed material of the high uniformity closed-cell silicone foaming silicone of the present invention under programmed temperature rise conditions;
[0065] Figure 3 These are waveforms of the apparent density and density deviation rate tests of the high-uniformity closed-cell silicone foaming silicone of the present invention, in both the embodiment and the comparative example.
[0066] Figure 4These are waveforms of closed-cell rate and water absorption rate tests for the high-uniformity closed-cell silicone foaming silicone of the present invention, in both the embodiment and the comparative example.
[0067] Figure 5 These are the tensile strength and tear strength test waveforms of the high-uniformity closed-cell silicone foam silicone examples and comparative examples of the present invention;
[0068] Figure 6 These are compression set waveforms of the high-uniformity closed-cell silicone foam silicone examples and comparative examples of the present invention. Detailed Implementation
[0069] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0070] Preparation Example 1:
[0071] This preparation example provides a method for preparing a microencapsulated silanol complex, comprising the following steps:
[0072] Diphenylsilanediol, used as the core material, methyl methacrylate monomer, used as the wall material prepolymer, and a crosslinking agent are mixed at a core-to-wall mass ratio of 1:0.5 to obtain a mixture.
[0073] The resulting mixture was then added to an aqueous solution containing polyvinyl alcohol dispersant and homogenized by high-speed shearing to form a microemulsion.
[0074] Subsequently, an initiator was added to the formed microemulsion, and the microemulsion was heated to the microencapsulation reaction temperature of 50°C. The mixture was stirred at a constant temperature for 2 hours to allow the monomers to polymerize and coat the surface of the silanol droplets to form coated products.
[0075] After the reaction was completed, the encapsulated product was cooled, filtered, washed and dried to obtain the microencapsulated silanol complex with a cell wall disruption temperature of 85°C.
[0076] Preparation Example 2:
[0077] This preparation example provides a method for preparing a microencapsulated silanol complex, comprising the following steps:
[0078] Diphenylsilanediol, used as the core material, methyl methacrylate monomer, used as the wall material prepolymer, and a crosslinking agent are mixed at a core-to-wall mass ratio of 1:1.2 to obtain a mixture.
[0079] The resulting mixture was then added to an aqueous solution containing polyvinyl alcohol dispersant and homogenized by high-speed shearing to form a microemulsion.
[0080] Subsequently, an initiator was added to the formed microemulsion, and the microemulsion was heated to the microencapsulation reaction temperature of 65°C. The reaction was carried out under constant temperature and stirring for 3.5 hours, so that the monomers polymerized and coated on the surface of the silanol droplets to form coated products.
[0081] After the reaction was completed, the encapsulated product was cooled, filtered, washed and dried to obtain the microencapsulated silanol complex with a cell wall rupture temperature of 92℃.
[0082] Preparation Example 3:
[0083] This preparation example provides a method for preparing a microencapsulated silanol complex, comprising the following steps:
[0084] Diphenylsilanediol, used as the core material, methyl methacrylate monomer, used as the wall material prepolymer, and a crosslinking agent are mixed at a core-to-wall mass ratio of 1:2.0 to obtain a mixture.
[0085] The resulting mixture was then added to an aqueous solution containing polyvinyl alcohol dispersant and homogenized by high-speed shearing to form a microemulsion.
[0086] Subsequently, an initiator was added to the formed microemulsion, and the microemulsion was heated to the microencapsulation reaction temperature of 80°C. The reaction was carried out under constant temperature and stirring for 5 hours, so that the monomers polymerized and coated on the surface of the silanol droplets to form coated products.
[0087] After the reaction was completed, the encapsulated product was cooled, filtered, washed and dried to obtain the microencapsulated silanol complex with a cell wall disruption temperature of 100℃.
[0088] Example 1:
[0089] This embodiment provides a highly uniform closed-cell silicone foam and its preparation method, including the following steps:
[0090] 100 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 3,000 mPa·s and a vinyl content of 0.10 wt% were added to a planetary mixing tank, nitrogen gas was introduced for protection, and the speed was set to 30 rpm.
[0091] Eight portions of HMDS (hexamethyldisilazane) hydrophobically treated and with a BET specific surface area of 150 m² were added in three batches. 2 / g of fumed silica with less than 0.5% Si-OH residue on the surface, with a 10min interval between batches;
[0092] Add 0.5 parts of a pre-diluted vinyl-functionalized MQ silicone resin with an M / Q value of 0.65, a vinyl content of 0.5 wt%, and a semi-transparent dispersion in vinyl-terminated polydimethylsiloxane, and continue stirring for 30 minutes until a uniform paste is formed.
[0093] Add 0.3 parts of KH-560 silane coupling agent for surface treatment, d 50 Ultrafine talc powder with a particle size of 1 μm was used as an inert nucleating seed crystal;
[0094] The microencapsulated silanol complex obtained in Preparation Example 1 was added as a sustained-release hydroxyl source (the amount added was such that the molar ratio of Si-H functional groups to active OH equivalents after mixing components A and B was 1:0.3).
[0095] Finally, a platinum catalyst with a Pt content of 3 ppm (added by diluting the terminal vinyl polydimethylsiloxane of the Karstedt catalyst with a Pt content of 3000 ppm), 0.05 parts of 1-ethynyl-1-cyclohexanol as the first inhibitor, and 0.02 parts of triphenylphosphine-platinum coordination complex that dissociates at 70 °C as the second inhibitor are added.
[0096] Degassing and stirring under a vacuum of -0.095 MPa for 20 min, followed by storage in a sealed container at ≤25℃ away from light to obtain component A;
[0097] Prepare a hydrogen-containing silicone oil with a Si-H content of 0.8 wt% and a viscosity of 15 mPa·s. Mix it with vinyl-terminated polydimethylsiloxane. By adjusting the proportion of the hydrogen-containing silicone oil, the total Si-H / vinyl functional group molar ratio of the final mixture of component A and component B is 1.5:1. Vacuum degassing and sealed storage are performed to obtain component B.
[0098] Next, the obtained component A and component B are dynamically degassed and mixed at a mass ratio of 100:4, with the mixing time controlled at 15 seconds. The uniformly mixed rubber compound is then injected into a preheated mold and foamed and vulcanized according to the following procedure:
[0099] Preheating and expansion at 75℃ for 60s reduces the viscosity of the system and causes the foaming reaction to occur first.
[0100] Next, cross-linking molding is carried out at 130℃ for 3 minutes, using the sudden temperature rise to quickly lock the cell structure;
[0101] Finally, a post-curing treatment was performed at 180℃ for 30 minutes to passivate residual bonds and remove volatiles;
[0102] After the foaming and vulcanization are completed, the molded product is demolded, then the edges are trimmed, and finally the performance is tested to obtain highly uniform closed-cell silicone foam.
[0103] Example 2:
[0104] This embodiment provides a highly uniform closed-cell silicone foam and its preparation method, including the following steps:
[0105] 100 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 10000 mPa·s and a vinyl content of 0.16 wt% were added to a planetary mixing tank, nitrogen gas was introduced for protection, and the speed was set to 45 rpm.
[0106] Twelve portions of HMDS (hexamethyldisilazane) hydrophobically treated with a BET specific surface area of 200 m² were added in three batches. 2 / g of fumed silica with less than 0.5% Si-OH residue on the surface, with a 10min interval between batches;
[0107] Add 1.4 parts of a pre-diluted vinyl-functionalized MQ silicone resin with an M / Q value of 0.75, a vinyl content of 1.2 wt%, and a semi-transparent dispersion in vinyl-terminated polydimethylsiloxane, and continue stirring for 45 minutes until a uniform paste is formed.
[0108] Add 0.8 parts of KH-560 silane coupling agent for surface treatment, d 50 Ultrafine talc powder with a particle size of 2 μm was used as an inert nucleating seed.
[0109] The microencapsulated silanol complex obtained in Preparation Example 2 was added as a sustained-release hydroxyl source (the amount added was such that the molar ratio of Si-H functional groups to active OH equivalents after mixing components A and B was 1:0.45).
[0110] Finally, a platinum catalyst with a Pt content of 7 ppm (added by diluting the terminal vinyl polydimethylsiloxane of the Karstedt catalyst with a Pt content of 5000 ppm), 0.14 parts of 1-ethynyl-1-cyclohexanol as the first inhibitor, and 0.08 parts of triphenylphosphine-platinum coordination complex that dissociates at 85 °C as the second inhibitor are added.
[0111] Degassing and stirring under a vacuum of -0.095 MPa for 20 min, followed by storage in a sealed container at ≤25℃ away from light to obtain component A;
[0112] Prepare a hydrogen-containing silicone oil with a Si-H content of 1.2 wt% and a viscosity of 50 mPa·s. Mix it with vinyl-terminated polydimethylsiloxane. By adjusting the proportion of the hydrogen-containing silicone oil, the total Si-H / vinyl functional group molar ratio of the final mixture of component A and component B is 2.0:1. Vacuum degassing and sealed storage are performed to obtain component B.
[0113] Next, the obtained component A and component B were dynamically degassed and mixed at a mass ratio of 100:7, and the mixing time was controlled to be 30 seconds.
[0114] Inject the well-mixed rubber compound into a preheated mold and proceed with the foaming and vulcanization process as follows: Preheat and expand at 85°C for 120 seconds to reduce the viscosity of the system and allow the foaming reaction to occur first.
[0115] Next, cross-linking molding is carried out at 150°C for 5 minutes, using the sudden temperature rise to quickly lock the cell structure;
[0116] Finally, a post-curing treatment was performed at 190℃ for 45 minutes to passivate residual bonds and remove volatiles.
[0117] After the foaming and vulcanization are completed, the molded product is demolded, then the edges are trimmed, and finally the performance is tested to obtain highly uniform closed-cell silicone foam.
[0118] Example 3:
[0119] This embodiment provides a highly uniform closed-cell silicone foam and its preparation method, including the following steps:
[0120] 100 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 30,000 mPa·s and a vinyl content of 0.25 wt% were added to a planetary mixing tank, nitrogen gas was introduced for protection, and the speed was set to 60 rpm.
[0121] Add 20 parts of D4Vi (tetramethyltetravinylcyclotetrasiloxane) treated with BET specific surface area of 300 m² in 3 batches. 2 / g of fumed silica with less than 0.5% Si-OH residue on the surface, with a 10min interval between batches;
[0122] Add 3.0 parts of pre-diluted vinyl-functionalized MQ silicone resin with an M / Q value of 0.85, a vinyl content of 2.0 wt%, and a semi-transparent dispersion in vinyl-terminated polydimethylsiloxane, and continue stirring for 60 min until a uniform paste is formed;
[0123] Add 2.0 parts of surface-treated with KH-560 silane coupling agent, d 50 5 μm ultrafine talc powder was used as an inert nucleating seed crystal; the microencapsulated silanol complex obtained in Preparation Example 3 was added as a slow-release hydroxyl source (the amount added was such that the molar ratio of Si-H functional groups to active OH equivalents after mixing components A and B was 1:0.6).
[0124] Finally, a platinum catalyst with a Pt content of 12 ppm (added by diluting the terminal vinyl polydimethylsiloxane of Karstedt catalyst with a Pt content of 8000 ppm), 0.3 parts of 3,5-dimethyl-1-hexyn-3-ol were added as the first inhibitor, and 0.15 parts of a reversible complex formed by a hindered phenol and platinum that dissociates at 95 °C were added as the second inhibitor.
[0125] Degassing and stirring under a vacuum of -0.095 MPa for 20 min, followed by storage in a sealed container at ≤25℃ away from light to obtain component A.
[0126] Prepare a hydrogen-containing silicone oil with a Si-H content of 1.8 wt% and a viscosity of 80 mPa·s. Mix it with vinyl-terminated polydimethylsiloxane. By adjusting the proportion of the hydrogen-containing silicone oil, the total Si-H / vinyl functional group molar ratio of the final mixture of component A and component B is 3.0:1. Vacuum degassing and sealed storage are performed to obtain component B.
[0127] Next, the obtained component A and component B were dynamically degassed and mixed at a mass ratio of 100:10, and the mixing time was controlled to be 50 seconds.
[0128] Inject the well-mixed rubber compound into a preheated mold and proceed with the foaming and vulcanization process as follows:
[0129] Preheating and expansion at 95℃ for 180s reduces the viscosity of the system and causes the foaming reaction to occur first.
[0130] Next, cross-linking molding was carried out at 165°C for 8 minutes, using the sudden temperature rise to quickly lock the cell structure;
[0131] Finally, a post-curing treatment was performed at 200℃ for 60 minutes to passivate residual bonds and remove volatiles;
[0132] After the foaming and vulcanization are completed, the molded product is demolded, then the edges are trimmed, and finally the performance is tested to obtain highly uniform closed-cell silicone foam.
[0133] Comparative Example 1:
[0134] Compared with Example 2, the difference is that the triphenylphosphine-platinum coordination complex that dissociates at 85°C is not added as a second inhibitor, otherwise the same.
[0135] Comparative Example 2:
[0136] Compared with Example 2, the difference is that the microencapsulated silanol complex, which serves as the source of sustained-release hydroxyl groups, is replaced with ordinary terminal hydroxyl silicone oil with an equivalent amount of active hydroxyl groups; all other aspects are the same.
[0137] Comparative Example 3:
[0138] Compared to Example 2, the difference is that no vinyl-functionalized MQ silicone pre-diluted solution is added, and an equal amount of end-vinyl polydimethylsiloxane with both ends vinyl-capped is used to make up the difference; otherwise, they are the same.
[0139] Comparative Example 4:
[0140] Compared with Example 2, the difference is that the preheating expansion process of maintaining 85°C for 120s during foaming and vulcanization is omitted. Instead, the uniformly mixed rubber compound is placed directly in an environment of 150°C for foaming and crosslinking reaction. All other aspects are the same.
[0141] Test Example 1:
[0142] The uncured rubber compounds that had just undergone dynamic degassing and mixing of components A and B in Example 2, Comparative Example 1, and Comparative Example 2 were used as rheological test objects; the rubber compounds after mixing in Example 2, Comparative Example 1, and Comparative Example 2 were used as thermodynamic analysis objects.
[0143] Dynamic rheological tests were conducted using a rotational rheometer. A parallel plate fixture with a diameter of 25 mm was selected, and the test gap was set to 1.0 mm. The strain was controlled at 1%, and the test frequency was 1 Hz. The temperature control program was set as follows: hold at 25 °C for 10 s, then increase the temperature to 85 °C at a rate of 60 °C / min and hold for 120 s, followed by increase the temperature to 150 °C at a rate of 60 °C / min and hold for 300 s. Data points showing the change of complex viscosity over time were recorded during the test.
[0144] Thermodynamic analysis was performed using differential scanning calorimetry (DSC). 5.0 to 6.5 mg of the mixed compound was weighed and placed in a standard aluminum crucible, which was then pressed into a tablet and sealed, with an empty aluminum crucible serving as a reference. Under a nitrogen atmosphere (gas flow rate of 50 mL / min), the temperature was continuously scanned from 25 °C to 200 °C at a heating rate of 10 °C / min. The change in heat flow rate of the sample during this process was recorded, and the peak temperatures of the endothermic and exothermic peaks were extracted.
[0145] Table 1. Summary of Dynamic Rheological and Thermal Analysis Characteristic Data
[0146] Test object Initial complex viscosity at 25℃ (Pa·s) Viscosity at the end of the isothermal period at 85℃ (Pa·s) Viscosity abrupt change start time (s) DSC endothermic peak temperature (°C) DSC exothermic peak temperature (°C) Example 2 118.4 82.6 142 92.4 136.7 Comparative Example 1 121.3 4852.1 74 91.8 95.2 Comparative Example 2 115.9 163.5 138 No obvious peak 134.1
[0147] Based on the data in Table 1 and Figure 1 The rheological curve trend of the mixed rubber compound in Example 2 shows that after the initial room temperature stabilization period, the complex viscosity of the mixed rubber compound shows a decreasing trend in the isothermal range of 85°C. Figure 1 The curve of Example 2 remained smooth in the early stage. According to Table 1, the viscosity change start time was 142s.
[0148] Figure 2The differential scanning calorimetry waveforms show a continuous trend of first absorbing heat and then releasing heat. Combined with the specific test values in Table 1, the endothermic peak in Example 2 corresponds to 92.4℃, and the exothermic peak corresponds to 136.7℃. The above chart characteristics reflect that the second inhibitor suppressed the cross-linking reaction during the isothermal stage, preserving a low-viscosity physical window for the cell wall disruption endothermic reaction and system expansion of the microencapsulated silanol complex.
[0149] For Comparative Example 1, Figure 1 The viscosity curve shows that it rises rapidly after entering the isothermal zone. The data in Table 1 indicates that the mutation start time is advanced to 74s, which indicates that the absence of a second inhibitor caused the rubber compound to crosslink prematurely before the expansion of the foaming gas.
[0150] The rheological curve of Comparative Example 2 showed significant fluctuations within the isothermal range, and Table 1 records that no effective endothermic peak was detected, reflecting that the use of ordinary hydroxyl-terminated silicone oil led to homogeneous boiling of the compound at low temperatures. Based on the comprehensive test data and waveform trends, the physicochemical responses of a dual-stage inhibitor and a microencapsulated sustained-release source in different temperature ranges were used to decouple the foaming and crosslinking reaction steps.
[0151] Test Example 2:
[0152] Highly uniform closed-cell silicone foam products that have undergone foaming vulcanization molding and edge trimming in Examples 1 to 3 and Comparative Examples 1 to 4 were used as test subjects.
[0153] Apparent density and density deviation rate tests were conducted. Five cubes measuring 30mm × 30mm × 10mm were randomly cut from the center and edge regions of the same test object. The mass of each specimen was determined using an analytical balance, and the actual dimensions were measured using vernier calipers to calculate the volume, thus obtaining the apparent density of each specimen. The arithmetic mean of the apparent densities of the five specimens was calculated as the average apparent density, and the percentage of the difference between the maximum and minimum values relative to the average value was calculated as the density deviation rate.
[0154] Closed-pore ratio tests were conducted. Approximately 15 cm³ of sample was cut from each test object. 3 A regular sample was placed in the sample chamber of a fully automated gas hydrometer. Using high-purity nitrogen as the test medium, the true skeletal volume of the sample was determined under isothermal conditions according to Boyle's law. The closed-porosity data was calculated by combining the apparent geometric volume of the sample.
[0155] Conduct a water absorption test. Cut each test object into 50mm×50mm×10mm samples and weigh the initial mass. Immerse the sample in distilled water at 25℃, ensuring the water level is 50mm above the sample surface. After soaking for 24 hours, remove the sample, blot the surface moisture with filter paper, and weigh it again. Calculate the percentage increase in sample mass relative to the initial mass and record it as the water absorption rate.
[0156] Table 2. Summary of Macroscopic Foaming Property Test Data for Examples and Comparative Examples
[0157] Test object Average apparent density (g / cm3) Density deviation rate (%) Closed-pore ratio (%) Water absorption rate (%) Example 1 0.421 2.1 94.3 1.82 Example 2 0.286 2.5 92.7 2.05 Example 3 0.174 3.2 91.4 2.41 Comparative Example 1 0.612 8.7 78.5 5.38 Comparative Example 2 0.315 14.3 42.6 24.71 Comparative Example 3 0.301 5.8 81.2 8.64 Comparative Example 4 0.358 11.4 55.3 17.52
[0158] Based on the test data in Table 2 and Figure 3 , Figure 4 The waveform trends shown indicate that the performance indicators of Examples 1 to 3 are generally within the optimal range. Figure 3 In the three embodiments, the solid lines of apparent density remain at a low level, and the corresponding dashed lines of density deviation rate smoothly approach the baseline; Figure 4 In the figure, the closed-cell rate represented by the solid line remains high, while the water absorption rate indicated by the dashed line is at a low level.
[0159] The aforementioned macroscopic performance confirms that the dual-stage inhibitor and microencapsulated silanol sustained-release source used in the formulation successfully constructed a reasonable crosslinking and foaming temperature window. Under this mechanism, in conjunction with the heterogeneous nucleation sites provided by inert nucleating seeds, bubbles achieved uniform growth in the matrix, effectively suppressing the merging and collapse of pores.
[0160] Based on the analysis of the comparative curve trends, it was found that the absence of a second inhibitor in Comparative Example 1 led to the failure of high-temperature masking, and the cross-linking speed was faster than the foaming speed. Figure 3 The apparent density curve showed an abnormally high peak. Comparative Example 2, which used ordinary terminal hydroxyl silicone oil to replace the microcapsule sustained-release source, failed to block the early reaction of the hydroxyl groups. Figure 4 The closed-cell rate curve showed a downward trend, while the water absorption rate curve showed an upward trend, confirming the destruction of the closed-cell structure by homogeneous boiling.
[0161] Comparative Example 3 omitted the vinyl-functionalized MQ silicone resin, resulting in the absence of the in-situ enriched resin crosslinking network at the cell wall membrane interface. This led to the membrane rupture when subjected to stress and expansion. Figure 4 The data shows that its closed-pore ratio fluctuates downwards.
[0162] Comparative Example 4 eliminated the preheating expansion process, and the direct high-temperature impact caused a disconnect between the curing process of the material's interior and exterior. Figure 3 and Figure 4 The waveform shows an increase in density deviation and a decrease in closed-cell rate. The correlation between the waveform trend and the data objectively reflects the actual control effectiveness of the raw material system and the staged temperature-controlled foaming process of this invention on the integrity of the macroscopic pore structure of the material.
[0163] Test Example 3:
[0164] The silicone foam products from Examples 1 to 3 and Comparative Examples 1 to 4, which were foamed and vulcanized and then left to stand at room temperature for 24 hours, were used as test subjects.
[0165] Basic mechanical property tests were conducted. Each test object was cut into dumbbell-shaped specimens (for tensile strength testing) and right-angled specimens (for tear strength testing) conforming to specifications using a punching machine, with a thickness controlled at 2.0 ± 0.2 mm. The specimens were clamped in the upper and lower fixtures of a universal testing machine, the tensile gauge length was set, and the test was conducted at a tensile speed of 500 mm / min. The maximum tensile force and maximum tear force at specimen fracture were recorded, and the tensile strength (MPa) and tear strength (kN / m) were calculated. Five parallel specimens were prepared for each group, and the arithmetic mean was taken.
[0166] Perform compression set tests. Cut cylindrical specimens with a diameter of 29.0 mm and a thickness of 12.5 mm from the flat area of each test object. Measure the initial center thickness of the specimen. Place the specimen in a compression fixture consisting of two parallel steel plates and a limiting block, and compress the specimen to 50% of its original thickness.
[0167] Place the fixture in a constant temperature drying oven set at 100℃ for 22 hours. Immediately after removing the fixture, unload the sample at room temperature and place it on a flat surface to recover freely for 30 minutes. Measure the center thickness again. Calculate the percentage of the unrecoverable thickness relative to the initial compression, which is the compression set value. Take the average of three parallel samples in each test group.
[0168] Table 3. Summary of Mechanical Properties and Compression Set Test Data of Examples and Comparative Examples
[0169] Test object Tensile strength (MPa) Tear strength (kN / m) Compression set (%) Example 1 1.12 5.86 14.3 Example 2 1.34 7.12 12.8 Example 3 0.97 4.95 16.7 Comparative Example 1 1.45 6.02 27.5 Comparative Example 2 0.38 2.14 52.4 Comparative Example 3 0.62 3.27 34.1 Comparative Example 4 0.74 3.81 29.6
[0170] Based on the data in Table 3 and Figure 5 , Figure 6 The waveform distribution trend shows that the tensile strength and tear strength in Examples 1 to 3 are in a relatively high value range. Figure 6 The solid waveform of compression permanent deformation corresponding to the region in the intermediate embodiment is in a low state (the test values are all below 17%).
[0171] The above test results reflect that the vinyl-functionalized MQ silicone resin introduced in the formulation of this invention is enriched in situ at the interface of the bubble pore wall and participates in the construction of the three-dimensional cross-linking network during the foaming and vulcanization cross-linking process.
[0172] The resin component enhances the thickness uniformity and structural toughness of the closed-cell membrane. Based on this reinforced pore network and high closed-cell ratio, the internal stress can be more evenly transmitted and dispersed when the material is subjected to long-term external compressive loads, avoiding microstructural fractures caused by local stress concentration, thus exhibiting a lower amount of irreversible deformation on a macroscopic scale.
[0173] The influence of each component can be further verified by comparing the data and waveforms of the comparative groups. Comparative Example 3, due to the absence of vinyl-functionalized MQ silicone resin, Figure 5 The intensity curve in the middle shows a significant dip, and Figure 6 The compression set waveform is at a relatively high level of 34.1%, indicating that the bubble wall lacking a resin reinforcement layer is prone to structural yielding under pressure.
[0174] Comparative Example 2, using a common hydroxyl source, resulted in foaming and boiling over, producing numerous open holes and structural defects. Its basic mechanical properties showed a severe decline, and the internal framework collapsed under pressure. Figure 6 The peak value was as high as 52.4%.
[0175] Although Comparative Examples 1 and 4 Figure 5 While exhibiting a certain basic tensile strength, uneven cell distribution due to process or formulation defects leads to microscopic wall film defects caused by a mismatch between foaming and crosslinking kinetics. Under high-temperature compression aging conditions at 100℃, these weak points yield, ultimately resulting in a reduction in the compression recovery capacity of this proportion.
[0176] Based on the comprehensive data and waveform trends, the resin reinforcement system in this embodiment of the invention, combined with a uniform foamed closed-cell structure, provides objective support for improving the mechanical load-bearing capacity and long-term dimensional stability of silicone materials.
Claims
1. A highly uniform closed-cell silicone foam, characterized in that, It is made by mixing component A and component B in a mass ratio of 100:(4-10) and then subjecting them to foaming vulcanization; Component A comprises the following raw materials in parts by weight: Vinyl-terminated polydimethylsiloxane: 100 parts; Hydrophobically treated fumed silica: 8-20 parts; Vinyl functionalized MQ silicone resin pre-diluted solution: 0.5-3.0 parts; Inert nucleating seed crystals: 0.3-2.0 parts; Microencapsulated silanol complex: The amount added is such that the molar ratio of Si-H functional groups to active OH equivalents after mixing component A and component B is 1:(0.3~0.6). Platinum catalyst: The amount added is such that the mass concentration of metallic platinum in component A is 3-12 ppm; First inhibitor: 0.05-0.3 parts; Second inhibitor: 0.02-0.15 parts; Component B is a compound mixture of hydrogen-containing silicone oil and the terminal vinyl polydimethylsiloxane. The amount of hydrogen-containing silicone oil is adjusted so that the total Si-H / vinyl functional group molar ratio after mixing component A and component B is (1.5~3.0):
1.
2. The highly uniform closed-cell silicone foaming material according to claim 1, characterized in that, The vinyl-terminated polydimethylsiloxane has a vinyl-terminated structure at both ends, a viscosity of 3,000–30,000 mPa·s, and a vinyl content of 0.10–0.25 wt%. The hydrophobically treated fumed silica is surface-treated with hexamethyldisilazane or tetramethyltetravinylcyclotetrasiloxane and has a BET specific surface area of 150–300 m². 2 Fumed silica with a surface Si-OH residue of less than 0.5% per g.
3. The highly uniform closed-cell silicone foaming material according to claim 1, characterized in that, The vinyl-functionalized MQ silicone resin pre-diluted solution has an M / Q value of 0.65 to 0.85 and a vinyl content of 0.5 to 2.0 wt%. The vinyl-functionalized MQ silicone resin in the pre-diluted solution is dissolved in the end-vinyl polydimethylsiloxane in a semi-transparent dispersion state. The inert nucleating seed crystals are ultrafine talc powder surface-treated with KH-560 silane coupling agent. 50 The particle size is 1–5 μm.
4. The highly uniform closed-cell silicone foam according to claim 1, characterized in that, The first inhibitor is 1-ethynyl-1-cyclohexanol or 3,5-dimethyl-1-hexyn-3-ol; The second inhibitor is a triphenylphosphine-platinum coordination complex that dissociates at 70–95 °C or a reversible complex formed by a sterically hindered phenol and platinum; The hydrogen-containing silicone oil has a Si-H content of 0.8–1.8 wt% and a viscosity of 15–80 mPa·s.
5. The highly uniform closed-cell silicone foam according to claim 1, characterized in that, The cell wall disruption temperature of the microencapsulated silanol complex is 85–100°C. The preparation method of the microencapsulated silanol complex includes: Diphenylsilanediol, used as the core material, methyl methacrylate monomer, used as the wall material prepolymer, and a crosslinking agent are mixed at a core-to-wall mass ratio of 1:(0.5-2.0) to obtain a mixture. The mixture is then added to an aqueous solution containing polyvinyl alcohol dispersant and homogenized to form a microemulsion; Subsequently, an initiator was added to the microemulsion and the mixture was polymerized and coated at a constant temperature of 50–80°C.
6. The highly uniform closed-cell silicone foam according to claim 1, characterized in that, The platinum catalyst is a diluent of terminal vinyl polydimethylsiloxane of Karstedt catalyst with a Pt content of 3000-8000 ppm.
7. A method for preparing highly uniform closed-cell silicone foam, characterized in that, The method for preparing a highly uniform closed-cell silicone foam as described in any one of claims 1 to 6 comprises the following steps: Add the vinyl-terminated polydimethylsiloxane into the stirring equipment, and under the protection of nitrogen, add the hydrophobically treated fumed silica and the pre-diluted vinyl-functionalized MQ silicone resin in batches, and stir to obtain a uniform paste. Subsequently, inert nucleating seeds, microencapsulated silanol complex, platinum catalyst, first inhibitor, and second inhibitor were added to the homogeneous paste. The mixture was then degassed and stirred under vacuum conditions and stored in a light-proof, sealed container to obtain component A. The hydrogen-containing silicone oil was compounded and mixed with the vinyl-terminated polydimethylsiloxane, and then vacuum degassed and sealed to obtain component B. The obtained component A and component B are dynamically degassed and mixed at a mass ratio of 100:(4-10) to obtain the adhesive compound; The rubber compound is injected into a mold for foaming and vulcanization. Finally, after demolding, trimming, and inspection, a highly uniform closed-cell silicone foam is obtained.
8. The preparation method according to claim 7, characterized in that, In the process of obtaining component A, the vacuum condition was -0.095 MPa, the degassing and stirring time was 20 min, and the obtained component A was stored in an environment not exceeding 25°C.
9. The preparation method according to claim 7, characterized in that, The foaming vulcanization process includes the following steps in sequence: Preheating expansion is carried out at 75–95℃ for 60–180 seconds. Cross-linking molding is performed at 130–165°C for 3–8 minutes. Post-curing treatment is performed at 180–200℃ for 30–60 minutes.
10. The preparation method according to claim 7, characterized in that, The dynamic degassing and mixing time is controlled to be 15-50 seconds, and then the adhesive is immediately injected into a mold preheated to 75-95°C.